Polypyrrole Wrapped V2O5 Nanowires Composite for Advanced Aqueous Zinc-Ion Batteries - Qin, Xinghua; Wang, Xinyu; Sun, Juncai; Lu, Qiongqiong; Omar, Ahmad; Mikhailova, Daria (Frontiers in Energy Research, 2020)
Aqueous zinc-ion batteries (ZIBs) have obtained increasing attention owing to the high safety, material abundance, and environmental benignity. However, the development of cathode materials with high capacity and stable cyclability is still a challenge. Herein, the polypyrrole (PPy)-wrapped V2O5 nanowire (V2O5/PPy) composite was synthesized by a surface-initiated polymerization strategy, ascribing to the redox reaction between V2O5 and pyrrole. The introduction of PPy on the surface of V2O5 nanowires not only enhanced the electronic conductivity of the active materials but also reduced the V2O5 dissolution. As a result, the V2O5/PPy composite cathode exhibits a high specific capacity of 466 mAh g–1 at 0.1 A g–1 and a superior cycling stability with 95% capacity retention after 1000 cycles at a high current density of 5 A g–1. The superior electrochemical performance is ascribed to the large ratio of capacitive contribution (92% at 1 mV s–1) and a fast Zn2+ diffusion rate. This work presents a simple method for fabricating V2O5/PPy composite toward advanced ZIBs.